Ultrasonic mediated synthesis of new benzo[a]phenoxazinium chlorides and their photophysical studies - Raju, B. Rama (2012)
Ultrasonic irradiation was demonstrated to be an efficient technique for activating various organic transformations, allowing short reaction times, high yields and sometimes good selectivity. Three new benzo[a]phenoxazinium chlorides possessing isopentylamino, (2-cyclohexylethyl)amino and phenethylamino groups at 5-position of the heterocyclic systems were efficiently synthesized under ultrasound irradiation. Photophysical characterization in ethanol and water, as well as acid-base equilibrium studies of the probes were carried out.